A study of employee’s job satisfaction in fast food restaurant in Klang Valley, Kuala Lumpur. - Ghazali, Hazrina; Ooi , Mei Ling; Ahmad, Faridah; Ishak, Maisarah (2012)
The main purpose of this study was to identify the employee’s job satisfaction in fast food restaurant in Klang Valley. This study also focused on the factors that contribute to employee’s job satisfaction. There were total 167 respondents who currently worked in fast food restaurant around Klang Valley participated in this study. Data was collected through self-administrated questionnaire by using convenience sampling. Descriptive and inferential statistics were utilized through the SPSS version 19.0 to analyze the data. Results showed that the respondents were somewhat satisfied towards their job with the average mean score of 3.66. The five organizational factors which were working conditions, pay and compensation, fairness, co-workers, and promotions were the significant predictors of job satisfaction in fast food restaurant (Sig. < 0.05). The study indicated that demographic characteristics such as gender, age, educational levels and job tenure were statistically insignificant in influencing the job satisfaction of employees. In addition, all the five organizational factors were found to be significantly correlated to employee’s job satisfaction (p < 0.001). It is recommended future study to compare the employee’s job satisfaction level between different types of restaurant and take into consideration of more variable that could affect employee’s job satisfaction. The findings hoped to help managers monitor their employee satisfaction level.